2009
DOI: 10.1111/j.1423-0410.2009.001215.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre experience with a simple blood salvage technique in patients with ruptured ectopic pregnancy in sub‐Sahelian West Africa

Abstract: The surgical treatment of ruptured ectopic pregnancy with intraperitoneal haemorrhage was rendered safe and efficient with this new salvaging equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…This study also reflects actually what happens in other countries in sub-Saharan Africa where Pruli,G. et al, carried similar multicentred study using patients with ruptured ectopic pregnancy [17]. Although it is becoming relativelyuncommon in developed countries due to current advances made in the blood screening processes, autologous blood transfusion constitutes about 5-10% of the total annual blood transfusion in the United States [12][13][14].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study also reflects actually what happens in other countries in sub-Saharan Africa where Pruli,G. et al, carried similar multicentred study using patients with ruptured ectopic pregnancy [17]. Although it is becoming relativelyuncommon in developed countries due to current advances made in the blood screening processes, autologous blood transfusion constitutes about 5-10% of the total annual blood transfusion in the United States [12][13][14].…”
Section: Discussionsupporting
confidence: 81%
“…However, very few studies have been done in sub-Saharan West Africa where IOBS method of autotransfusion was used to correct anaemia due to haemorrhage from ruptured ectopic pregnancy in two hundred and twelve patients (212). This study showed that autologous blood transfusion did not only improve the haemoglobin concentration of the severely anaemic patients but was a safe method of blood transfusion with minimal TTIs [17].…”
Section: Hematology and Leukemia Issn 2052-434xmentioning
confidence: 70%
“…The experience in St. John of God Hospital, Tanguiéta, Benin Republic in salvaging intraperitoneal blood with a perforated metallic conical funnel in 212 patients has shown that the incidence of allogenic blood use is reduced. The postoperative hemoglobin level increased to 84.7 ± 10.5 g/L 6 days postoperatively from a preoperative level of 70.6 ± 18.7 g/L after the transfusion of 681 ± 389 mL (n = 212) of salvaged blood 96. A review97 showed that intraoperative blood salvage (IBS) and ABT is a simple, effective, and safe method of blood replacement and that its use should be of primary consideration in the management of ruptured ectopic pregnancy.…”
Section: Challenges Of Suboptimal Use Of Nonpharmacologic and Pharmacmentioning
confidence: 82%
“…Thus, implementation of alternatives to donor blood transfusion, such as salvage autotransfusion, has been considered. 3,4 Intravenous (IV) iron administration has been shown to be a useful tool for correcting anemia in a variety of clinical settings. 5 Once the patient is stabilized, full correction of postpartum anemia may be attained by administration of iron therapy with or without human recombinant erythropoietin.…”
Section: Introductionmentioning
confidence: 99%